New ecological and economic process to save energy by electromagnetic fields. (2022) - Mghaiouini, Redouane; abdelhadi, Mortadi; Saifaoui, Dennoun; Salah, Mohammed; abderrahmane, Elmlouky; ghaouti Chahid, El; El Jouad, Zouhair; Kandoussi, Khalid; Zari, Rkia; Monkade, Mohamed; El Bouari, Abdeslam
Abstract: The evaporation temperature of salt water was measured as a function of time under the action of low frequency electromagnetic fields of 40 mT. According to our results, the evaporation of saline water for different concentrations of magnetized sodium chloride (NaCl) increased slightly compared to untreated saline water. A probable explanation for this phenomenon is the breaking of hydrogen bonds by the electromagnetic field. A second interpretation is that the Lorentz force can increase the surface induction of ripples, resulting in a reduction in surface tension and therefore a change in the thermal behavior of magnetized salt water. Herein, we have based on the control of the water magnetization operation, and we have insisted on precision of measures of the thermal parameters, in order to investigate about the impact of magnetic field on them. All experimental results have been treated by statistical tools in order to reveal the interaction between the different parameters measured.